Color changes in yardang strata sediment in the Dunhuang Yardang National Geopark, Northwest China: Controlling factors and significance for sedimentary environments - Liang, Xiaolei; Wang, Xiaoli; Zhai, Xiaohui; Niu, Qinghe; Li, Jiyan (Frontiers in Earth Science, 2023)
Color, being one of the most intuitive, easily accessible, and important lithological indicators, can be used to identify yardang strata sedimentary environments. However, the lack of quantitative analysis and systematic research have limited how chromatic environmental proxies can be extracted and interpreted. The Dunhuang Yardang National Geopark was selected for this experiment. Based on chromaticity, grain-size, chemical element, organic matter, and carbonate content measurements of yardang strata sediment samples, this study used correlation analysis and chromaticity proxy extraction to quantitatively characterize associated color changes, controlling factors, and sedimentary environments. Results found significant cyclic changes in chromaticity parameter curves were observed in the profiles, which is likely indicative of a dry/wet evolutionary process that occurred during different stages of the yardang sedimentary environment. Organic matter content was the main factor affecting changes in brightness, while iron oxide content directly affected yardang sediment redness and yellowness values. Due to its low value, effects of carbonate content on brightness were obscured. The grain-size characteristics indirectly affect the brightness value through the content of quartz, feldspar and organic matter. Moreover, based on modern analogy method, the brightness and redness values are proved to be effective proxies for distinguishing the yardang sedimentary environment. Accordingly, it is concluded that the sedimentary environment of Dunhuang yardang landforms is composed of sedimentation that derived from lacustrine, aeolian, and alluvial environments, and that the chromaticity parameter range and characteristic color for sedimentary environments are extracted and quantified. Findings from this study not only rectify the lack of quantitative research on yardang sediment color theory but also provide an important theoretical basis for identifying sedimentary environments in the field.